(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The development of expertise is the product of a positive relationship between genetics, psychology and sociology. This study explores educational and cultural conditions impacting sports skill development. Work on the consistency and quantity of preparation indicates that these two factors are main predictors of achievement. Therefore, it is important to provide services such as parental help and appropriate coaching. The determinants of sporting ability are often known as social variables such as cultural biases and the relative age impact. Although environmental factors are certainly essential for the development of sports, more work is urgently required.